2013
DOI: 10.1007/s40257-013-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Wound Dressings: Selecting the Most Appropriate Type

Abstract: Appropriate wound dressing selection is guided by an understanding of wound dressing properties and an ability to match the level of drainage and depth of a wound. Wounds should be assessed for necrosis and infection, which need to be addressed prior to selecting an ideal dressing. Moisture-retentive dressings include films, hydrogels, hydrocolloids, foams, alginates, and hydrofibers and are useful in a variety of clinical settings. Antimicrobial-impregnated dressings can be useful in wounds that are superfici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
147
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(151 citation statements)
references
References 51 publications
1
147
0
3
Order By: Relevance
“…Several reviews had summarized and analyzed the merits of polymer hydrogels applied for wound care [18][19][20][21]. In our previous work CHI hydrogels were prepared by using natural genipin as crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews had summarized and analyzed the merits of polymer hydrogels applied for wound care [18][19][20][21]. In our previous work CHI hydrogels were prepared by using natural genipin as crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, antimicrobial agents like silver sulfadiazine, iodine or medical grade honey have been incorporated into dressings as a way of keeping the wounds safe from infections. However, many studies have shown that treatment with these agents alone is not sufficient to achieve complete wound healing and in some cases, toxicity problems can ensue [9].…”
Section: Introductionmentioning
confidence: 99%
“…17 On the other hand, traditional bandages can be used as secondary dressings (as cover of primary ones) in combination with moistureretentive and antibacterial-impregnated systems. 21 Moisture-retentive dressings include films, hydrogels, hydrocolloids and foams. Semi-permeable and transparent films are typically indicated for superficial and lightly exudative wounds, and first-degree burns.…”
Section: Selection Of Commercially Available Dressingsmentioning
confidence: 99%